Causes, management and complications of ascites: a review (International Current Pharmaceutical Journal, 2015)
Ascites is the pathological state in which fluid accumulates in the peritoneal cavity. Fluid accumulation may be due to infection and malignancy or due to other diseases like liver disease, heart failure, and renal disease. The ascitic fluid can be graded into Transudative and Exudative fluid based on the serum ascites albumin gradient (SAAG). The prominent cause of ascites is found to be Liver Cirrhosis. The most common symptom of Ascites is recent weight gain, increased abdominal girth and dyspnea. The first line treatment of ascites includes education regarding dietary sodium restriction and oral diuretics. However, other mechanical methods can also be used if the patient is unresponsive to this approach. But, there are some limitations while using these mechanical methods. Ascites is also associated with certain complications like spontaneous bacterial perotinitis, hepatorenal syndrome and dilutional hyponatremia. Ascites itself is not fatal unless it becomes infected. So, early diagnosis and effective treatment should be ensured in order to avoid further complications. This review focuses on the grades, causes, symptoms, management and complications of Ascites.DOI: http://dx.doi.org/10.3329/icpj.v4i3.21936 International Current Pharmaceutical Journal, February 2015, 4(3): 370-377